2011
DOI: 10.1016/j.jconrel.2011.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of skin resealing after insertion of microneedles in human subjects

Abstract: Over the past decade, microneedles have been shown to dramatically increase skin permeability to a broad range of compounds by creating reversible microchannels in the skin. However, in order to achieve sustained transdermal drug delivery, the extent and duration of skin‘s increased permeability needs to be determined. In this study, we used electrical impedance spectroscopy to perform the first experiments in human subjects to analyze the resealing of skin‘s barrier properties after insertion of microneedles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
185
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(204 citation statements)
references
References 42 publications
15
185
2
2
Order By: Relevance
“…The electrical impedance technique, Figure 7, exploits the SC's electrical insulating properties to provide information on skin barrier function and confirm if MNs have successfully compromised the SC [48]. A strong inverse correlation between skin permeability and skin electrical impedance has been demonstrated [58,60]. Yan et al [6] recognised a linear relationship between acyclovir flux and the inverse of skin electrical resistance.…”
Section: Electrical Impedance Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The electrical impedance technique, Figure 7, exploits the SC's electrical insulating properties to provide information on skin barrier function and confirm if MNs have successfully compromised the SC [48]. A strong inverse correlation between skin permeability and skin electrical impedance has been demonstrated [58,60]. Yan et al [6] recognised a linear relationship between acyclovir flux and the inverse of skin electrical resistance.…”
Section: Electrical Impedance Methodsmentioning
confidence: 98%
“…Assessing MN piercing of the skin, and the corresponding insertion force required to cause successful penetration, has been investigated by a number of groups through the use of electrical impedance methods [41,44,48,58,59]. In this context, impedance is the phase dependant resistance of the skin to the flow of alternating current.…”
Section: Electrical Impedance Methodsmentioning
confidence: 99%
“…[30] The kinetics of pore resealing after microneedle insertion have been studied in human subjects by electrical impedance measurements, which showed that pores formed by microneedles recovered their barrier properties within 2 h when the skin was not occluded, but took 3 to 40 h to recover when the skin was occluded, depending on the geometry of the microneedles. [31,32] The kinetics of pore resealing were also studied in hairless rats using TEWL and tissue staining, and showed similar timeframes for pore resealing. [33] For the present vibrating microneedles, 5 min of application time was optimal for the transdermal delivery of vitamin C. Skin irritation scores for vitamin C gel were zero, which indicated the safety and acceptability of vibrating microneedles for transdermal administration of vitamin C gel.…”
Section: Discussionmentioning
confidence: 95%
“…In the case of manufacturing laboratories, the assumption is that any application to human skin occurs as a result of accident and that there will therefore be no prior treatment. It has been shown that the potential for bacterial infection arising from microneedle applications is considerably lower when compared with conventional injection systems [9,28], and, under non-occlusive conditions, the microchannels would be expected to heal within 2 h of the initial puncture [29]. The situation becomes more ambiguous where there is a failure in the dissolution or removal of a dissolvable/swellable microneedle such that partially dissolved needle fragments continue to bridge the skin barrier [1].…”
Section: Discussionmentioning
confidence: 99%